Factors Influencing SIMRS Quality at Al-Islam H.M Mawardi General Hospital - Solihin, Ahmad; Nisak, Umi Khoirun (Universitas Muhammadiyah Sidoarjo, 2024)
This quantitative study investigates the impact of organizational factors on Hospital Management Information Systems (HMIS), employing the PRISM framework. The absence of a search menu linked to the primary key of national identity number in the HMIS was scrutinized for its effects. Results reveal significant influences of organizational factors on technical and behavioral aspects of HMIS. Notably, periodic evaluations by the IT team significantly enhance technological advancements within hospitals, while frequent training sessions for HMIS users markedly improve their comprehension of system functionalities. These findings underscore the pivotal role of organizational strategies in shaping the effectiveness and efficiency of HMIS, offering valuable insights for optimizing healthcare information management practices. Highlights : Organizational factors significantly influence technical enhancements in Hospital Management Information Systems. Frequent evaluations by the IT team contribute to technological advancements within hospital systems. Regular user training sessions enhance comprehension and utilization of HMIS functionalities Keywords: Hospital Management Information Systems, Organizational Factors, PRISM Analysis, Technology Improvement, User Training